Examining the relevance of parent-adolescent relationships in the romantic relationship quality of young adults - Drake, Adryanna Siqueira (Kansas State University, 2013)
This study prospectively examined how parent-adolescent relationships influence romantic relationship quality of offspring, utilizing the National Longitudinal Survey of Adolescent Health (ADD Health, n = 3,946). Further, this study investigated whether self-esteem and depression symptoms mediated these relationships, and if gender was a significant moderator. Adolescent girls who perceived their relationships with their mothers and fathers to be strong were more likely to have better quality romantic relationships as young adults. This relationship was found to be direct and indirect, through the effect of self-esteem. Adolescent boys who perceived their relationship with their father to be strong and whose mothers were more knowledgeable about them were less likely to experience depression symptoms as young adults, and in turn, to have better quality romantic relationships. Adolescent boys whose mothers perceived to have a strong relationship with them had higher self-esteem as young adults. Finally, there were significant differences between boys and girls in that the association between mother knowledge and depression symptoms was stronger for boys. Results support the stability of parent-adolescent relationships in influencing future relationships and highlight the importance of parent-adolescent relationships in predicting psychological wellbeing and romantic relationship quality.
Keywords: Parenting; Adolescent; Romantic relationship quality; Psychology (0621)